Lecturers’ Perspective on The Ethics of Student Verbal Communication at Islamic Religious Universities and Public Universities in East Java - Ahmadi, Ahmadi; Putri, Weni Tria Anugrah (Program Studi Pendidikan Agama Islam, 2020)
Communication is a daily activity in academic or non-academic activities within the university. This study aims to explore the lecturer perspective on the ethics of verbal communication students. This study is a qualitative research with a phenomenological study method. To simplify the design of the research, the qualitative research stages chosen were Spradley's. This research data collection technique is through interviews conducted with lecturers who served in a number of universities in East Java Province. While the data collection instruments used are structured interview guidelines and unstructured interview guidelines. Sampling in this study was conducted using non-probability sampling techniques. More precisely by using the type of purposive and snowball sampling. The data generated is in the form of secondary primary data. Primary data in the form of conversations with appointed lecturers. Whereas secondary data is obtained when interviewing key informants. One of the results of this study is that it is known that the current use of telephones for communication between students and lecturers is declining. One reason is the reluctance of lecturers to receive phone calls from students who are sudden. With these findings it is hoped that there will be student attention to their ethics in communicating with lecturers.